Strategi Implementasi Program Desa Bersinar dalam Penanganan Desa Zona Merah Narkoba: Studi Kasus di Desa Ringinarum, Kabupaten Kendal - Lisamaulina Safitri; Marsekal Vero Herivo; Vina Ainun Nadhiroh; Muhammad Daffa Fathurrahman; Izyan Nur Faundria; M Amirul Zidan; Asifur Rohman; Muhammad Faiq (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
Handling drug trafficking in rural areas is a serious challenge in Indonesia, especially in villages classified as "red zones". Ringinarum Village, Kendal Regency, is a clear example of a village that faces a significant drug threat. This research aims to analyze in depth the strategy for implementing the Bersinar Village Program in dealing with villages that fall into the red zone category, with a special focus on Ringinarum Village. Using a qualitative approach and case study method, this research evaluates the effectiveness of the Bersinar Village Program in increasing community awareness and participation in rehabilitation efforts. The research results show that this program has succeeded in increasing public awareness of the importance of drug treatment, as well as increasing their active participation in rehabilitation programs. Collaboration between the Kendal Regency National Narcotics Agency (BNN) and village officials is the key to success, with the vital role of village officials as the main driver. This research confirms the importance of adapting programs to local contexts for higher effectiveness in dealing with drugs in rural areas.